2011
DOI: 10.5007/1980-0037.2011v13n3p223
|View full text |Cite
|
Sign up to set email alerts
|

Efeito discriminante da morfologia e alcance de ataque no nível de desempenho em voleibolistas. DOI: 10.5007/1980-0037.2011v13n3p223

Abstract: The measures were compared between the two groups using the Student t-test for independent samples. Discriminant function analysis was applied to predict group allocation using the measures obtained as independent variables. The two groups differed significantly in terms of body weight, fat mass, height, maximum attack height, range of attack, and somatotype. Discriminant function analysis identified the somatotype measures (endomorphy, ectomorphy, and mesomorphy) with correlation coefficients below 0.30. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
6
0
3
Order By: Relevance
“…In another research was evaluated 40 volleyball athletes performing the power test (vertical jump test -Sargent Test adapted) resulting in the first group composed of 21 athletes 43.58 ± 5.32 cm and the second group composed of 19 athletes 44.47 ± 3.67 cm. It is observed that the explosive strength of the lower limbs quantified by the height of the vertical jump, did not present significant difference between the groups 19 .…”
Section: Discussionmentioning
confidence: 80%
“…In another research was evaluated 40 volleyball athletes performing the power test (vertical jump test -Sargent Test adapted) resulting in the first group composed of 21 athletes 43.58 ± 5.32 cm and the second group composed of 19 athletes 44.47 ± 3.67 cm. It is observed that the explosive strength of the lower limbs quantified by the height of the vertical jump, did not present significant difference between the groups 19 .…”
Section: Discussionmentioning
confidence: 80%
“…Cabral et al 16 in their study, evaluated 40 volleyball athletes performing potency test (vertical jump test -Sergeants adapted Test) resulting for the first group consisting of 21 athletes 43.58 ± 5.32 cm and the second group compound 19 athletes 44.47 ± 3.67 cm. It is observed that the explosive force of lower limbs quantified by the vertical jump height, showed no significant difference between groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, as opposed to standing up volleyball, the players in sitting volleyball are recruited from population of persons with disabilities, regardless of morphological and motor predispositions usually preferred with volleyball players, such as longitudinal dimensionality of skeleton, explosive strength, coordination and above all agility. Characteristic which has negative impact on the success of the game is subcutaneous adipose tissue (Cabral, B., Cabral, S., Miranda, Dantas & Reis, 2011;Dopsaj, Nešić & Ćopić, 2010;Marelić, Đurković & Rešetar, 2007). Sitting volleyball can be played by male and female players with damaged movement system which includes classification of International Organisation of Sports for the Disabled (IOSD) for persons with amputations and classifications for other damages of musculoskeletal system (les autres), such as: cerebral palsy, damage to the spinal column, dwarfism, dysmelia, hip and knee arthroplasty with permanent disabilities and similar.…”
Section: Introductionmentioning
confidence: 99%